Forming limit curves analysis of aluminum alloy considering the through-thickness normal stress, anisotropic yield functions and strain rate. (October 2016) - Mirfalah-Nasiri, S.M.; Basti, A.; Hashemi, R.
Abstract: Based on three anisotropic yield functions including Karafillis–Boyce (K–B), Yld96 and Yld2011, directional normalized uniaxial yield stresses, directional r-value and forming limit curve (FLC) for AA3104-H19 aluminum alloy under plane stress condition are numerically investigated in this article. Moreover, considering the through-thickness normal stress effect the forming limit diagram (FLD), stress-based forming limit diagram (FLSD) and extended forming limit stress diagram (XFLSD) is also studied theoretically based on Yld2011 yield criterion and modified Marciniak–Kuczynski (M–K) model. The nonlinear equations set are solved through employing Newton–Raphson numerical method to calculate limiting strains. The anisotropic plastic behavior and FLC of AA3104-H19 predicted by Yld2011 yield criterion are in good agreement with experimental data and are more accurate than those of K–B and Yld96 yield functions. In addition, according to FLD, the formability of sheet metal increases by applying the through-thickness normal stress. The effects of strain rate at quasi-static condition and temperature are theoretically investigated on the FLD of AA3104 aluminum alloy. The positive temperature sensitivity and negative strain rate sensitivity are observed of FLD of AA3104. Highlights: Yield stresses, r-value and FLD for AA3104-H19 are investigated by employing the K-B, Yld96 and Yld2011 criterions. The M–K model is modified by considering the through-thickness normal stress. Based on the Yld2011 yield criterion, the effect of through-thickness normal stress is studied on the FLD, FLSD and XFLSD. The anisotropic plastic behavior and FLC of AA3104-H19 predicted by Yld2011 is in good agreement with experimental data. The FLD of AA3104 exhibits the negative strain rate sensitivity and positive temperature sensitivity.